2013
DOI: 10.1108/jmp-12-2012-0397
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in personality predictors of counterproductive behavior

Abstract: PurposeThe purpose of this study is to examine gender differences in personality predictors of a specific form of workplace aggression: counterproductive work behaviors directed at individuals (CWB‐I).Design/methodology/approachStudents (n=212) who were part‐time employees working at least 15 hours per week completed a measure of the five‐factor model (FFM) personality traits and two circumplex personality traits (Calmnesss and Pleasantness), as well as a measure of CWB‐I. Hierarchical regressions and tests of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 71 publications
(107 reference statements)
2
21
0
Order By: Relevance
“…In accordance with the conservation of resources theory, emotional stability is a resource which can be utilized to reduce behavioral strain. The results support earlier studies which revealed that the lack of emotional stability leads to engagement in WDB (Gonzalez-Mulé et al, 2013;Hudson et al, 2012;Kluemper et al, 2015). Less emotionally stable individuals are more likely to encounter negative emotional states, such as anxiety, depression and anger that could trigger them to behave deviantly under stress and the behaviors displayed include behaviors such as tardiness, absenteeism and withholding effort.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In accordance with the conservation of resources theory, emotional stability is a resource which can be utilized to reduce behavioral strain. The results support earlier studies which revealed that the lack of emotional stability leads to engagement in WDB (Gonzalez-Mulé et al, 2013;Hudson et al, 2012;Kluemper et al, 2015). Less emotionally stable individuals are more likely to encounter negative emotional states, such as anxiety, depression and anger that could trigger them to behave deviantly under stress and the behaviors displayed include behaviors such as tardiness, absenteeism and withholding effort.…”
Section: Discussionsupporting
confidence: 80%
“…A less emotionally stable individual tends to exhibit deviant behavior (Gonzalez-Mulé et al, 2013;Hudson et al, 2012) such as poor work attitude, tardiness, absenteeism and withholding effort. Nair and Bhatnagar (2011) proposed an integrated general model of WDB, in which, besides organizational factors, individual factors including dispositional factors are associated with WDB.…”
Section: Emotional Stability As a Moderatormentioning
confidence: 99%
“…While comparing mean reports of men and women has pointed to inconsistent results (e.g., Black, 1990;Gonzalez-Mulé, et al, 2013;Hershcovis et al, 2007), the present findings reveal that employees' gender predicts differential forms of interpersonal and organizational deviance and demonstrate the unique value in employing the profile analysis capable of discovering such patterns. Theorists and practitioners should be aware of the relevance of gender not to the mere question who is more prone to workplace deviance -men or women -, but rather what types of negative acts we may expect from the two genders and what are the organizational experiences that encourage them to display these acts.…”
Section: Limitationsmentioning
confidence: 90%
“…Further, interactions between gender and personality traits were assessed in predicting counterproductive work behaviors directed at individuals. Specifically, agreeableness and pleasantness were found to be negative predictors among men (but not women), whereas emotional stability was a negative predictor among women (but not men) (Gonzalez-Mulé, DeGeest, Kiersch, & Mount, 2013). On the other hand, Hershcovis et al's (2007) meta-analysis of workplace aggression indicated that there is little gender difference with respect to indirect forms of aggression.…”
Section: Perfiles De Género De Desviación Individual Y Organizacionalmentioning
confidence: 99%
“…This phenomenon provokes dysfunctional effects both on individuals and organizations such as managerial costs, turnover, and productivity decrease. 1 This assertion becomes even more significant for those organizations that are mainly composed by employees who provide particular assistance to citizens in a close and direct way.…”
mentioning
confidence: 97%